Top-down approach to estimating the nitrogen footprint of food in Japan. (July 2017) - Shindo, Junko; Yanagawa, Akane
Highlights: A new method for estimation of nitrogen footprint of food was developed. Top-down approach evaluates new nitrogen inputs due to fertilizer and BNF. Without using VNF facilitates the estimation for heavy food importer countries. Food trade significantly reduces Japanese nitrogen footprint. Abstract: In this paper, we propose a new methodology for estimating the nitrogen footprint of food, which has recently been identified as an indicator of human interference in the environment, specifically due to our global production and consumption of food. N-calculator is the common method of nitrogen footprint estimation, which evaluates nitrogen outputs into the environment at each step from crop production to food consumption based on Virtual Nitrogen Factor (VNF). For heavy food importers like Japan, however, it is difficult to get suitable VNFs of exporting countries. Our method is a top-down approach for estimating new external nitrogen inputs from chemical fertilizers and biological nitrogen fixation (BNF) used within the country (i.e., direct inputs), as well as in food-exporting countries (i.e., indirect inputs) that export to Japan; our approach is based primarily on open access statistical data, not on VNFs. In this present study, we measured nitrogen inputs for 110 combinations of food items and exporting countries; from our evaluations, the estimated nitrogen footprint of Japan was 16.5–18.1 kg N capita −1, of which direct inputs constituted approximately 5.5 kg N, leaving more than two-thirds as indirect inputs from food imports. The nitrogen footprint of Japan was smaller than those of the USA and some European countries, but we calculated the nitrogen footprint to be 27.8 kg N capita −1, i.e., larger than all other countries, when all consumed food was assumed to be produced in Japan, and the significant increase in nitrogen input was caused primarily by less efficient crop production in Japan than by exporting countries. Overall, our results were much smaller than previous estimations of footprint of Japan based on the common method in which all imported food is assumed to come from the USA because of the difficulty in using VNFs for many exporting countries. Although our results have uncertainties, based on our results, we consider our method to be suitable for estimating the nitrogen footprint of countries that significantly rely on imported food, much like Japan.